2020
DOI: 10.1016/j.ejmp.2020.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a dose calculation algorithm based on Monte Carlo simulations for treatment planning towards MRI guided ion beam therapy

Abstract: Magnetic resonance guidance in particle therapy has the potential to improve the current performance of clinical workflows. However, the presence of magnetic fields challenges the current algorithms for treatment planning. To ensure proper dose calculations, compensation methods are required to guarantee that the maximum deposited energy of deflected beams lies in the target volume. In addition, proper modifications of the intrinsic dose calculation engines, accounting for magnetic fields, are needed. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…More recently, a detailed simulation and experimental study was conducted, which used a proton beamline, coupled with a small research dipole magnet in a perpendicular configuration. 19 This work demonstrated the feasibility of modified treatment planning to account for the localized near fringe and main 1 T magnetic field of a 12.5 cm pole gap dipole magnet. In their work, the particle source was located at 522 mm from the surface of the dosimetry phantom, and the magnetic field model covered a range up to 122 mm outside the phantom.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…More recently, a detailed simulation and experimental study was conducted, which used a proton beamline, coupled with a small research dipole magnet in a perpendicular configuration. 19 This work demonstrated the feasibility of modified treatment planning to account for the localized near fringe and main 1 T magnetic field of a 12.5 cm pole gap dipole magnet. In their work, the particle source was located at 522 mm from the surface of the dosimetry phantom, and the magnetic field model covered a range up to 122 mm outside the phantom.…”
Section: Introductionmentioning
confidence: 77%
“…More recently, a detailed simulation and experimental study was conducted, which used a proton beamline, coupled with a small research dipole magnet in a perpendicular configuration 19 . This work demonstrated the feasibility of modified treatment planning to account for the localized near fringe and main 1 T magnetic field of a 12.5 cm pole gap dipole magnet.…”
Section: Introductionmentioning
confidence: 95%
“…The concept of MRintegrated proton therapy (MRiPT) and its design have been explored by several groups, [9][10][11] and feasibility studies have been conducted using both simulations 10 and experiments. [12][13][14][15] When analytical dose calculation models are concerned, analytical solutions to the deflected trajectory of a slowing-down proton beam in a magnetic field 16,17 and detailed modeling of the lateral beam profiles, including not only the Gaussian shape of the central core but also the low-dose tails, 18,19 are required as in the case without magnetic fields. 20,21 Unlike X-rays, where only the trajectories of secondary electrons are affected by the magnetic field, primary protons undergo deflections or rotations under transverse or longitudinal magnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted by Padilla-Cabal et al, 18 the low-dose tail of the lateral profile was modeled and validated using Monte Carlo simulation (MCS) and an experiment using a research dipole magnet. 19 They showed that the asymmetry of the low-dose tail between the inward and outward beam sides is more pronounced under a strong magnetic field. They also proposed two independent and exponential tailed functions, which successfully described the distorted lateral beam profiles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation